A zirconium alloy hot extrusion gradientized lubricating coating material and method of use thereof
Patent Information
- Application Number
- CN202411337898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-09-25
AI Technical Summary
但采用紫铜等软金属包覆,易造成润滑的不连续,且挤压后需酸洗掉铜皮,工序繁杂;而玻璃润滑剂高温粘度波动范围大,在热挤压时玻璃粉易发生脱落和不规则流动,导致润滑失效
[0007]本发明通过调控润滑涂料中二硫化钼、石墨、二硫化钨与粘结剂的比例使涂层具有优异的润滑性能,利用固化工艺保证涂层与工件的结合强度且在挤压完成后易从工件上去除。通过抗氧化涂料及SiO2外壳包覆形成对氧气阻隔,防止润滑相在高温下与空气接触而氧化失效,实现高温下优异的润滑性能。通过调控抗氧涂料中玻璃粉与硅酸钠的配比,可以使得涂层在长时间的保温下仍具有稳定性,保温时间越长涂层越均匀致密,防止润滑成分及工件被氧化。
Smart Images

Figure CN119350892B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lubrication materials technology, specifically relating to a zirconium alloy hot-extruded gradient lubrication coating material and its application method. Background Technology
[0002] Nuclear power, recognized worldwide as a clean energy source, is characterized by high efficiency, safety, and economy. Zirconium alloys, with their excellent corrosion resistance, small thermal neutron absorption cross-section, and good compatibility with uranium fuel, have become indispensable materials in nuclear reactors. However, zirconium alloys are susceptible to contamination by elements such as oxygen, nitrogen, and hydrogen during hot extrusion processes. Furthermore, they exhibit high deformation resistance, poor fluidity, and a tendency to stick to molds, placing high demands on the lubrication process during processing.
[0003] In actual production, zirconium alloys are typically lubricated using either soft metal cladding or glass lubricants. However, cladding with soft metals like copper can lead to discontinuous lubrication, and the copper plating needs to be removed by acid washing after extrusion, making the process complex. Glass lubricants, on the other hand, have a wide viscosity range at high temperatures, and the glass powder is prone to shedding and irregular flow during hot extrusion, leading to lubrication failure. Solid lubricant coatings are sometimes used to aid extrusion production, but there is currently limited research in China on solid lubricant coatings suitable for temperatures between 680℃ and 780℃. Chinese patent application (CN 110157521 A) discloses a material for lubrication and thermal protection in hot extrusion of zirconium alloys. At 750℃, the friction factor measured using the circular compression method is approximately 0.2, indicating a relatively high friction coefficient. Furthermore, in actual production, zirconium alloy billets coated with lubricant need to be heated to the processing temperature and held at that temperature for a period of time before being fed into the extrusion cylinder. Therefore, higher requirements are placed on the coating's ability to maintain good lubrication performance under prolonged high-temperature conditions. Thus, researching a lubricant coating suitable for long-term heat treatment at high temperatures is extremely necessary. Summary of the Invention
[0004] The first objective of this invention is to provide a zirconium alloy hot-extruded gradient lubricating coating material, and the second objective of this invention is to provide a method for using the lubricating coating material.
[0005] The first objective of this invention is achieved by providing a zirconium alloy hot-extruded gradient lubricating coating material, which is composed of a lubricating coating and an anti-oxidation coating. The lubricating coating is composed of the following raw materials in parts by weight: 10-22 parts of MoS2@SiO2 composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water. The antioxidant coating is composed of the following raw materials in parts by weight: 12-18 parts of fast-dissolving powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water.
[0006] The second objective of this invention is achieved as follows: the method of using the zirconium alloy hot-extruded gradient lubricating coating material specifically involves immersing the zirconium alloy fully in the lubricating coating for 5-10 seconds, then removing it, allowing it to stand at room temperature for 5-10 minutes, and then transferring it to an oven at 200-220°C for heating and curing for 20-30 minutes. After cooling, it is then fully immersed in the anti-oxidation layer material for 5-10 seconds, then removed, allowed to stand at room temperature for 5-10 minutes, and then transferred to an oven for two heating and curing cycles to obtain the gradient lubricating coating.
[0007] This invention achieves excellent lubrication performance by controlling the ratio of molybdenum disulfide, graphite, tungsten disulfide, and binder in the lubricating coating. A curing process ensures strong adhesion between the coating and the workpiece, and the coating is easily removed from the workpiece after extrusion. An antioxidant coating and a SiO2 shell form an oxygen barrier, preventing the lubricating phase from oxidizing and failing at high temperatures, thus achieving excellent lubrication performance at high temperatures. By controlling the ratio of glass powder to sodium silicate in the antioxidant coating, the coating maintains stability even after prolonged heat treatment; the longer the heat treatment time, the more uniform and dense the coating becomes, preventing oxidation of the lubricating components and the workpiece.
[0008] The zirconium alloy hot extrusion gradient lubricating coating provided by this invention can exhibit excellent lubrication performance at temperatures up to 760°C and can extend the heat preservation time of the workpiece before processing. This invention effectively solves the problem in actual production where the effectiveness of the lubricating coating often necessitates prolonged heat preservation, leading to uneven temperature distribution in zirconium alloy workpieces and hindering smooth processing. The coating of this invention is non-volatile, produces no chemical pollution, and is non-toxic. After extrusion, the coating peels off as the workpiece cools. Figure 4 This facilitates cleaning after processing. Attached Figure Description
[0009] Figure 1 A scanning electron microscope image of the cross-section of the coating prepared in Example 1; Figure 2 This is a macroscopic view of the coating in Embodiment 1 of the present invention; Figure 3 A scanning electron microscope image of the coating prepared in Example 2; Figure 4 This is a peeling image of the coating after cooling in Embodiment 1 of the present invention; Figure 5 Friction coefficient curves of the coating prepared in Example 1 after being kept at 700℃ and 760℃ for 10 min respectively; Figure 6 Friction coefficient curves of the coating prepared in Example 1 after being kept at 700℃ and 760℃ for 30 min respectively; Figure 7 Friction coefficient curves of the coating prepared in Example 1 after being kept at 700℃ and 760℃ for 60 min respectively; Figure 8 The friction coefficient curves of commercially available lubricating materials for Comparative Example 1 after heat treatment at 700℃ for 10 min and 30 min are shown. Figure 9 The friction coefficient curves of the coating in Comparative Example 2 after being kept at 700℃ for 10 min and 30 min are shown. Detailed Implementation
[0010] The present invention will be further described below with reference to embodiments, but this is not intended to limit the present invention in any way. Any modifications or substitutions made based on the teachings of the present invention shall fall within the protection scope of the present invention.
[0011] This invention relates to a zirconium alloy hot-extruded gradient lubricating coating material, which is composed of a lubricating coating and an anti-oxidation coating. The lubricating coating is composed of the following raw materials in parts by weight: 10-22 parts of MoS2@SiO2 composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water. The antioxidant coating is composed of the following raw materials in parts by weight: 12-18 parts of fast-dissolving powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water.
[0012] The preparation method of the MoS2@SiO2 composite material is as follows: 1) Sodium molybdate, thioacetamide and cetyltrimethylammonium bromide in a mass ratio of 16:18:1-16:21:1 were added to deionized water, and after thorough ultrasonic dispersion and stirring, the mixture was transferred to a reaction vessel. The mixture was heated to 210-220°C at a heating rate of 10°C per minute and kept at that temperature for 24-30 hours. After cooling in the furnace, the mixture was centrifuged, the precipitate was collected, washed and dried to obtain MoS2 spheres with a particle size of 300-400 nanometers. 2) Disperse the MoS2 spheres obtained in step 1) in an 85% ethanol solution at a mass ratio of 1:32-1:40. Then add tetraethyl orthosilicate and ammonia water at a volume ratio of 1:20-1:25 between the tetraethyl orthosilicate and the dispersed solution. Stir continuously at 420-450 r / min for 24-30 hours. After completion, centrifuge at 5000-6000 rpm for 15-20 min, collect the precipitate, wash and dry it to obtain the MoS2@SiO2 composite material.
[0013] In step 1), the ultrasonic dispersion power is 300-400W, and the ultrasonic time is 1-4h; In step 2), the volume ratio of tetraethyl orthosilicate to ammonia is 2:1 to 3:2.
[0014] The glass powder comprises, by mass fraction: 31-29 parts lead dioxide, 14-12 parts silicon dioxide, 3-2 parts aluminum oxide, and 1-0.5 parts boron trioxide.
[0015] The volume ratio of tetraethyl orthosilicate to ammonia is 2:1 to 3:2.
[0016] The lubricating coating is prepared as follows: MoS2@SiO2 composite material, aluminum dihydrogen phosphate, graphite, tungsten disulfide, and deionized water are mixed and ultrasonically stirred. The ultrasonic power is 300W-400W, the stirring speed is 700-750r / min, and the stirring time is 1-2 hours.
[0017] The preparation method of the antioxidant coating is as follows: Add fast-dissolving powdered sodium silicate to deionized water and stir continuously at 450-600 r / min for 2-3 hours at 35-45℃; add low softening point glass powder, raise the temperature to 50-55℃, and stir continuously at 600-650 r / min for 2-3 hours to obtain the material of the antioxidant layer.
[0018] The present invention also provides a method for using the zirconium alloy hot extrusion gradient lubricating coating material, specifically, the zirconium alloy is fully immersed in the lubricating coating for 5-10 seconds, then removed, left to stand at room temperature for 5-10 minutes, and then transferred to an oven at 200-220℃ for heating and curing for 20-30 minutes. After cooling, it is fully immersed in the anti-oxidation layer material for 5-10 seconds, then removed, left to stand at room temperature for 5-10 minutes, and then transferred to an oven for two heating and curing cycles to obtain the gradient lubricating coating.
[0019] The two-stage curing method is as follows: First, raise the temperature to 80-85℃ at a rate of 10-12℃ per minute and hold for 10-15 minutes. Then, raise the temperature to 200-210℃ at a rate of 10-15℃ per minute and hold for 20-30 minutes. Example 1 1. Preparation of MoS2@SiO2 composite material: 1) Sodium molybdate, thioacetamide and cetyltrimethylammonium bromide in a mass ratio of 16:18:1 were added to deionized water, fully ultrasonically dispersed and stirred evenly, and then transferred to a reaction vessel. The mixture was heated to 210°C at a heating rate of 10°C per minute and kept at that temperature for 24 hours. After cooling in the furnace, the mixture was centrifuged, the precipitate was collected, washed and dried to obtain MoS2 spheres with a particle size of 300-400 nanometers. 2) Take 8 portions of the MoS2 spheres obtained in step 1) and add them to an 85% ethanol solution. Disperse the mixture ultrasonically at 300-400W for 4 hours. Add tetraethyl orthosilicate and ammonia in a volume ratio of 3:2. Stir continuously at 450 rpm for 24 hours. After completion, centrifuge at 6000 rpm for 15 minutes, collect the precipitate, wash and dry it to obtain the MoS2@SiO2 composite material. The mass ratio of MoS2 spheres to ethanol solution is 1:32, and the volume ratio of ethanol solution to tetraethyl orthosilicate is 20:1.
[0020] 2. By mass fraction, 10 parts of MoS2@SiO2 composite material, 6 parts of aluminum dihydrogen phosphate, 12 parts of graphite, 8 parts of tungsten disulfide and 76 parts of deionized water were ultrasonically vibrated and continuously stirred at 700 r / min for 1 hour to obtain an effective lubricating coating.
[0021] 3. By mass fraction, add 18 parts of instant-soluble powdered sodium silicate to 47 parts of deionized water, and stir continuously at 450 r / min for 2 hours at 35°C to obtain solution B. 4. Add 30 parts of low softening point glass powder to the above solution B, raise the temperature to 50°C, and stir continuously at 600 r / min for 2 hours to obtain an antioxidant coating.
[0022] In use, the zirconium alloy extruded rod is fully immersed in the lubricating coating for 5-10 seconds, then removed and placed vertically at room temperature to allow the coating to flow and level quickly and evenly, covering the surface of the rod and resulting in a uniform coating thickness. The specimen is then placed in an oven and heated to 200°C at a rate of 2°C per minute. After standing at 200°C for 20 minutes, aluminum dihydrogen phosphate undergoes a transformation to form a reinforcing structure, improving the bonding strength between the lubricating layer and the substrate. After the above operations are completed, the rod is removed and allowed to stand for 10 minutes to cool down. Then, the rod is slowly immersed in the anti-oxidation coating for 5-10 seconds. After removal, it is allowed to stand at room temperature for 5 minutes to allow the coating to evenly cover the surface of the specimen. Subsequently, the specimen is heated in an oven at a rate of 10°C per minute to 80°C and held for 10 minutes, then heated at a rate of 10°C per minute to 200°C and held for 20 minutes. The lubricating layer and the anti-oxidation layer diffuse into each other, forming a gradient structure coating, such as... Figure 1 As shown.
[0023] Figure 4 The image shows the peeling of the coating after cooling in Example 1. Due to the changes in the coefficient of thermal expansion, lattice strain, and Young's modulus caused by surface effects during the heating and cooling of the coating and zirconium alloy substrate, the thermal strain causes the coating to automatically peel off. Furthermore, the peeling ability increases with increasing processing temperature, which is beneficial for subsequent surface cleaning and treatment after zirconium alloy processing, simplifying the process steps.
[0024] Example 2 1. By mass fraction, 22 parts of MoS2@SiO2 composite material, 12 parts of aluminum dihydrogen phosphate, 6 parts of graphite, 2 parts of tungsten disulfide and 46 parts of deionized water were ultrasonically vibrated and continuously stirred at 700 r / min for 1 hour to obtain an effective lubricating coating.
[0025] 2. By mass fraction, add 12 parts of instant-soluble powdered sodium silicate to 58 parts of deionized water, and stir continuously at 450 r / min for 2 hours at 35°C to obtain solution B. 3. Add 35 parts of low softening point glass powder to the above solution B, raise the temperature to 50°C, and stir continuously at 600 r / min for 2 hours to obtain an antioxidant coating.
[0026] In use, the zirconium alloy extruded rod is fully immersed in the lubricating coating for 5-10 seconds, then removed and placed vertically at room temperature to allow the coating to flow and level quickly and evenly, covering the surface of the specimen and ensuring a uniform coating thickness. The specimen is then placed in an oven and heated to 200°C at a rate of 2°C per minute. After standing at 200°C for 20 minutes, aluminum dihydrogen phosphate undergoes a transformation to form a reinforcing structure, improving the bonding strength between the lubricating layer and the substrate. After the above operations are completed, the rod is removed and allowed to stand for 10 minutes to cool down. Then, the rod is slowly immersed in the anti-oxidation coating for 5-10 seconds. After removal, it is allowed to stand at room temperature for 5 minutes to allow the coating to evenly cover the surface of the specimen. Subsequently, the specimen is heated in an oven at a rate of 10°C per minute to 80°C and held for 10 minutes, then heated at a rate of 10°C per minute to 200°C and held for 20 minutes. The lubricating layer and the anti-oxidation layer diffuse into each other, forming a gradient structure, such as... Figure 2-3 As shown.
[0027] Example 3 1. Preparation of MoS2@SiO2 composite material: 1) Sodium molybdate, thioacetamide and cetyltrimethylammonium bromide in a mass ratio of 16:21:1 were added to deionized water, fully ultrasonically dispersed and stirred evenly, and then transferred to a reaction vessel. The mixture was heated to 220°C at a heating rate of 10°C per minute and kept at that temperature for 24 hours. After cooling in the furnace, the mixture was centrifuged, the precipitate was collected, washed and dried to obtain MoS2 spheres with a particle size of 300-400 nanometers. 2) Take 5 portions of the MoS2 spheres obtained in step 1) and add them to an 85% ethanol solution. Disperse the mixture ultrasonically at 400W for 2 hours. Add tetraethyl orthosilicate and ammonia in a volume ratio of 2:1. Stir continuously at 420 rpm for 30 hours. After completion, centrifuge at 5000 rpm for 20 minutes, collect the precipitate, wash and dry it to obtain the MoS2@SiO2 composite material. The mass ratio of MoS2 spheres to ethanol solution is 1:40, and the volume ratio of ethanol solution to tetraethyl orthosilicate is 1:25.
[0028] 2. By mass fraction, 16 parts of MoS2@SiO2 composite material, 9 parts of aluminum dihydrogen phosphate, 9 parts of graphite, 5 parts of tungsten disulfide, and 50 parts of deionized water were ultrasonically vibrated and continuously stirred at 750 r / min for 2 hours to obtain an effective lubricating coating.
[0029] 3. By mass fraction, add 15 parts of instant-soluble powdered sodium silicate to 52 parts of deionized water, and stir continuously at 600 r / min for 2 hours at 45°C to obtain solution B. 4. Add 32 parts of low softening point glass powder to the above solution B, raise the temperature to 55°C, and stir continuously at 600 r / min for 2 hours to obtain an antioxidant coating.
[0030] In use, the zirconium alloy extruded rod is fully immersed in the lubricating coating for 5-10 seconds, then removed and placed vertically at room temperature to allow the coating to flow and level quickly and evenly, covering the surface of the rod and resulting in a uniform coating thickness. The specimen is then placed in an oven and heated to 200°C at a rate of 2°C per minute. After standing at 220°C for 30 minutes, aluminum dihydrogen phosphate undergoes a transformation to form a reinforcing structure, improving the bonding strength between the lubricating layer and the substrate. After the above operations are completed, the rod is removed and allowed to cool down. Then, the rod is slowly immersed in the anti-oxidation coating for 5-10 seconds. After removal, it is left to stand at room temperature for 10 minutes to allow the coating to evenly cover the surface of the specimen. Subsequently, the specimen is heated in an oven at a rate of 15°C per minute to 85°C and held for 15 minutes. Then, the temperature is increased to 210°C at a rate of 15°C per minute and held for 30 minutes. The lubricating layer and the anti-oxidation layer diffuse into each other, forming a gradient structure lubricating coating.
[0031] Comparative Example 1 Take a certain amount of imported zirconium alloy hot pressurization special lubricant M currently on the market, and mix 1 part M with 2 parts deionized water by weight. Then, perform ultrasonic oscillation and stir continuously at 700 r / min for 1 hour to obtain a lubricating coating.
[0032] When using this method, immerse the zirconium alloy extruded rod fully in the lubricating coating for 5-10 seconds, remove it, and place it upright at room temperature to allow the coating to flow evenly and cover the surface of the specimen. Then, place the specimen in an oven and heat it to 200°C at a rate of 2°C per minute, and let it stand for 20 minutes to complete the curing process and obtain the lubricating coating.
[0033] Comparative Example 2 In this comparative example, the lubricating material used is the same as in Example 1, but the difference lies in the preparation method of the lubricating coating.
[0034] The preparation method of the lubricating coating in Comparative Example 2 is as follows: 1. Immerse the zirconium alloy extruded rod fully in the lubricating coating prepared in Example 1 for 5-10 seconds, remove it, and place it vertically at room temperature to allow the coating to flow and level quickly and evenly, covering the surface of the specimen and ensuring a uniform coating thickness. Then, place the specimen in an oven and heat it to 200°C at a rate of 2°C per minute. Let it stand at 200°C for 20 minutes to allow aluminum dihydrogen phosphate to transform and form a reinforcing structure, improving the bonding strength between the lubricating layer and the substrate. 2. After the above operations are completed, remove the rod and let it stand for 10 minutes to cool down. Then, slowly immerse the specimen in the anti-oxidation coating for 5-10 seconds. After removing it, let it stand at room temperature for 15 minutes to allow the coating to evenly cover the surface of the specimen and cure to obtain a lubricating coating.
[0035] Detection Example 1 1. The tribological properties of the lubricating coating prepared in Example 1 were tested using an MFT-5000 (RTEC, USA) high-temperature friction testing machine. The load was 10 N, the rotation speed was 30 r / min, the rotation radius was 15 mm, and the corresponding linear velocity was approximately 47 mm / s. The paired spheres were silicon nitride ceramic spheres (radius 9.525 mm). The friction experiments were conducted at 700℃ and 760℃ for 10 min, 30 min, and 60 min, respectively, with the friction cycle lasting 180 s. The real-time friction coefficient was recorded. Each experiment was repeated at least three times. The experimental results are as follows: Figure 5-7 As shown.
[0036] Results analysis: From Figure 5-7 It can be seen that within a holding time of less than 30 minutes, the friction coefficient of the lubricating coating in Example 1 remains consistently below 0.2, reaching a minimum of 0.08. The lubricating coating in Example 1 also maintains excellent performance after holding at 760℃ for 60 minutes, with an average friction coefficient close to 0.1, fully meeting the processing requirements for hot extrusion of zirconium alloys.
[0037] 2. The tribological properties of the lubricating coatings prepared in Comparative Examples 1-2 were tested using an MFT-5000 (RTEC, USA) high-temperature friction testing machine. The load was 10 N, the rotation speed was 30 r / min, the rotation radius was 15 mm, and the corresponding linear velocity was approximately 47 mm / s. The paired spheres were silicon nitride ceramic spheres (radius 9.525 mm). The friction experiments were conducted at 700℃ for 10 min and 30 min respectively, with the friction cycle lasting 180 s. The real-time friction coefficient was recorded. Each experiment was repeated at least three times. The experimental results are as follows: Figure 8-9 As shown.
[0038] Results analysis: From Figure 8 It can be seen that the friction coefficient of the lubricating coating in Comparative Example 1 is higher than 0.2, and the friction coefficient fluctuates greatly after long-term heat preservation, indicating unstable performance.
[0039] The average friction coefficient of the lubricating coating in Comparative Example 2 is around 0.2. Under the same experimental conditions, its tribological performance is worse than that of the coating obtained by two-step heating and curing in Example 1.
[0040] In summary, the lubricating coating prepared by this invention exhibits excellent and stable lubrication performance at 760℃, and can extend the heat preservation time of the workpiece before processing.
Claims
1. A zirconium alloy hot-extruded gradient lubricating coating, characterized in that, The lubricating coating is made of a lubricating paint and an antioxidant paint; The lubricating coating is composed of the following raw materials in parts by weight: 10-22 parts of MoS2@SiO2 composite material, 6-12 parts of aluminum dihydrogen phosphate, 6-12 parts of graphite, 2-8 parts of tungsten disulfide, and 46-76 parts of deionized water. The antioxidant coating is composed of the following raw materials in parts by weight: 12-18 parts of fast-dissolving powdered sodium silicate, 30-35 parts of low softening point glass powder, and 47-58 parts of deionized water. The method for preparing the lubricating coating is as follows: Immerse the zirconium alloy fully in the lubricating coating for 5-10 seconds, then remove it and let it stand at room temperature for 5-10 minutes. Then, transfer it to an oven at 200-220℃ for 20-30 minutes to cure. After cooling, immerse it fully in the anti-oxidation coating for 5-10 seconds, then remove it and let it stand at room temperature for 5-10 minutes. Then, transfer it to an oven for two heating and curing cycles to obtain a gradient lubricating coating. The two heating and curing methods are as follows: first, heat the coating at a rate of 10-12℃ per minute to 80-85℃ and hold for 10-15 minutes, then heat the coating at a rate of 10-15℃ per minute to 200-210℃ and hold for 20-30 minutes.
2. The zirconium alloy hot-extruded gradient lubricating coating according to claim 1, characterized in that, The preparation method of the MoS2@SiO2 composite material is as follows: 1) Sodium molybdate, thioacetamide and cetyltrimethylammonium bromide in a mass ratio of 16:18:1~16:21:1 were added to deionized water, and after thorough ultrasonic dispersion and stirring, the mixture was transferred to a reaction vessel. The mixture was heated to 210~220℃ at a heating rate of 10℃ per minute and kept at that temperature for 24~30 hours. After cooling in the furnace, the mixture was centrifuged, the precipitate was collected, washed and dried to obtain MoS2 spheres with a particle size of 300~400nm. 2) Disperse the MoS2 spheres obtained in step 1) in an 85% ethanol solution with a mass ratio of MoS2 spheres to ethanol solution of 1:32 to 1:
40. Then add tetraethyl orthosilicate and ammonia water with a volume ratio of tetraethyl orthosilicate to ethanol solution of 1:20 to 1:
25. Stir continuously at 420 to 450 r / min for 24 to 30 hours. After completion, centrifuge at 5000 to 6000 rpm for 15 to 20 minutes, collect the precipitate, wash and dry it to obtain the MoS2@SiO2 composite material.
3. The zirconium alloy hot-extruded gradient lubricating coating according to claim 2, characterized in that, In step 1), the ultrasonic dispersion power is 300~400W and the ultrasonic time is 1~4h; in step 2), the volume ratio of tetraethyl orthosilicate to ammonia is 2:1~3:
2.
4. The zirconium alloy hot-extruded gradient lubricating coating according to claim 1, characterized in that, The raw materials of the low softening point glass powder, by mass parts, include: 29-31 parts lead dioxide, 12-14 parts silicon dioxide, 2-3 parts aluminum oxide, and 0.5-1 parts boron trioxide.
5. The zirconium alloy hot-extruded gradient lubricating coating according to claim 1, characterized in that, The lubricating coating is prepared as follows: MoS2@SiO2 composite material, aluminum dihydrogen phosphate, graphite, tungsten disulfide and deionized water are mixed and ultrasonically stirred to obtain the coating.
6. The zirconium alloy hot-extruded gradient lubricating coating according to claim 5, characterized in that, The ultrasonic power is 300W~400W, the stirring speed is 700~750r / min, and the stirring time is 1~2 hours.
7. The zirconium alloy hot-extruded gradient lubricating coating according to claim 1, characterized in that, The method for preparing the antioxidant coating is as follows: add fast-dissolving powdered sodium silicate to deionized water and stir continuously at 450-600 r / min for 2-3 hours at 35-45℃; add low softening point glass powder, raise the temperature to 50-55℃, and stir continuously at 600-650 r / min for 2-3 hours to obtain the antioxidant coating.
8. A method for preparing the zirconium alloy hot extrusion gradient lubricating coating as described in claim 1, characterized in that, The zirconium alloy is fully immersed in the lubricating coating for 5-10 seconds, then removed and left to stand at room temperature for 5-10 minutes before being transferred to an oven at 200-220°C for 20-30 minutes to cure. After cooling, it is fully immersed in the anti-oxidation coating for 5-10 seconds, then removed and left to stand at room temperature for 5-10 minutes before being transferred to an oven for two heating and curing cycles to obtain a gradient lubricating coating. The two-stage curing method is as follows: First, raise the temperature to 80-85℃ at a rate of 10-12℃ per minute and hold for 10-15 minutes. Then, raise the temperature to 200-210℃ at a rate of 10-15℃ per minute and hold for 20-30 minutes.
Citation Information
Patent Citations
Material for zirconium alloy hot extrusion lubrication and heat protection, preparation and application method
CN110157521A
Water-based lubricating agent for titanium alloy hot extrusion forming
CN107653051A
Lubricant as well as preparation method and application thereof
CN112779074A